0609 Sleep Stabilization in Prehypertensive/Hypertensive Patients. (25th May 2022) - Stokes, Alicia; Yang, Huan; Buraks, Olivia; Vazquez, Michael; Pandeya, Sarbesh; Haack, Monika; Mullington, Janet
Abstract: Introduction: Variable sleep/wake patterns have been linked to increased cardiometabolic risk. The current project investigates the effects of using sleep hygiene interventions to stabilize sleep timing in prehypertensive/hypertensive patients. Growing evidence supports the importance of regularizing sleep timing in improving cardiovascular health, and we believe that using sleep hygiene techniques to stabilize sleep may reduce these risks. Methods: As part of a larger study, fifty-three participants (55.5 ± 1.4 years; 51% male) completed sleep diaries during 3 study periods. The first period (S1) was a baseline control, the second period (S2) was a 4-week wait-list control condition, and the third period (S3) was an 8-week randomly assigned intervention that used sleep hygiene approaches and scheduling to stabilize sleep timing or stabilize and lengthen sleep. Currently, we are still blind to condition; however, because both conditions involve sleep stabilization, an analysis using linear mixed models was used to assess change in the variability of total sleep time (SDTST), wake up time (SDWUT), and fall asleep time (SDFAT) across the 3 study periods. Results: There was a significant decrease in SDTST variability (standard deviation) at post-intervention (S3) compared to S2 (p<0.01) and S1 (p<0.01). There was also a significant decrease in SDWUT variability at post-intervention (S3) compared to S2 (p<0.01) and S1 (p<0.01). There was a trend towards a significantly decreased SDFAT at S3 compared to S2 (p=0.057), but there was a significant decrease in SDFAT variability during S3 compared to S1 (p<0.01). Conclusion: These data suggest that we were able to utilize sleep hygiene interventions to decrease the variability in total sleep time, wake-up time and fall asleep time. When we unblind we will report on if we were able to increase and lengthen the sleep period for those in the sleep extension condition. Support (If Any): NIH (R01HL125379 to Dr. Janet Mullington), Harvard Catalyst, Harvard Clinical and Translational Science Center (UL1TR001102)